A Team Allocation Decision for Aircraft Fleet Maintenance - Pereira, Duarte (2021)
This paper is about a computer application for planning maintenance of aircraft fleet in what regards allocation of skilled technicians. The formalization for this planning is a mathematical programming problem written as a minimizing one. The decision variables are the allocation of the skilled technicians. The data are the number of available technicians, the working hours needed to accomplish maintenance, the costs due to the daily operation of facilities, and due to the fleet downtime. Although, the formalization is of a non-linear integer-programming problem, a transformation of variables from positive integer ones to Boolean ones is conceivable and allows a reformulation as a pure integer linear programming problem. Also, a relaxation of the integer variables to continuous ones allows for a relaxed formulation as a convex non-linear programming problem. A case study of two fleets illustrates both formulations: solved by the pyomo library calling the GLPK for the pure linear integer programming problem and calling solvers in Scipy library for the relaxed formulation. An inference presented about the results of the case study addresses the issue of using nonlinear programming to emulate the solution of linear integer programming.